Increased plasticity of non-classic Th1 cells toward the Th17 phenotype. Issue 5 (2nd September 2020) - Leipe, Jan; Pirronello, Fausto; Klose, Antonia; Schulze-Koops, Hendrik; Skapenko, Alla
Abstract: Objectives: To analyze occurrence and plasticity of two recently described distinct subtypes of Th1 cells named classic (CD161−/CCR6−) and non-classic (CD161+/CCR6+) Th1 cells in early rheumatoid arthritis (RA) patients and healthy controls (HCs). Methods: Frequencies of in vivo -generated Th1 cell populations were assessed after cytokine secretion assay for IFNγ/IL-17 and surface staining for CD161/CCR6. Viable Th1 cells (IFNγ+IL-17−) were sorted into classic Th1 (CD161-CCR6−) and non-classic Th1 (CD161+CCR6+) cells, trans-differentiated under different Th cell-inducing conditions, and assessed for plastic changes by analyzing the Th cell-associated cytokine and transcription factor profiles. Results: Ex vivo frequencies of classic (CD161−CCR6−) and non-classic (CD161+CCR6+) Th1 cells as well as related Th1 cell subpopulations CD161+CCR6− and CD161−/CCR6+ did not differ significantly between RA and HCs. However, trans-differentiation of ex vivo non-classic (CD161+CCR6+) and CD161−/CCR6+ Th1 cells resulted in a substantial shift toward Th17 and Th1/Th17 phenotypes, particularly under Th17-inducing conditions. In contrast, classic (CD161−/CCR6−) and CD161+CCR6− Th1 cells showed higher plasticity towards IL-4-producing cells, most of them shifting to a Th1/Th2 phenotype. Conclusion: Whereas non-classic (CD161+/CCR6+) and CD161-CCR6+ Th1 cells demonstrated an increased plasticity towards IL-17- phenotypes, classic Th1 and CD161+CCR6− Th1 cells showed more plasticity towards IL-4-producing phenotypes.